Decreasing Total Amount of Defects at the Rectification Area by Improving Reparation Process (A Case Study at PT. XYZ) - Heinrich Putra; S. Awibowo; A.R. Ahmad (JURNAL TEKNIK INDUSTRI, 2019)
Abstract – Defect is one of the most problems in car manufacturer especially in PT. XYZ. Paint Problem, Scratch, Dent, Shortage, Gap and Transition are some problems which usually found in the assembly process. Those problems are caused by many factors: shipment, logistic or even assembly process itself. Thus, there must be some ideas or ways to be developed to decrease total problems in the assembly process. The purpose of decreasing total defects in the assembly line is because there are too many cars park and wait at the rectification area to get repaired. Therefore, this research is one of many ways that can reduce the amount of defects in the cars by improving In-Line and Shadow Station Rework concept which means to repair or rework light defect such as small scratch and paint problem. In addition, there is supporting tools called B-Pillar protector to prevent damages at the most problematic part (B-Pillar) at the station which contributes the most damage. With this method and supporting tool, PT.XYZ hopes total defect cars at the end of assembly line will reduce.